Cariprazine Safety in Adolescents and the Elderly: Analyses of Clinical Study Data - Szatmári, Balázs; Barabássy, Ágota; Harsányi, Judit; Laszlovszky, István; Sebe, Barbara; Gál, Mónika; Shiragami, Kazushi; Németh, György (Frontiers in Psychiatry, 2020)
Schizophrenia is a life-long mental disorder, affecting young adolescents to elderly patients. Antipsychotic treatment is indicated for all patients with schizophrenia, including the very young and old as well. Developmental issues in the young and decline in organ functioning in the elderly could influence reactions to the drug, and require different dosing regimens. The aim of the present article was to examine the safety profile and dosing requirements in adolescent (13 to less than 18) and elderly (65 and above) patients treated with cariprazine. Data from two clinical studies (one pharmacokinetic pediatric study and one phase III clinical trial) on 49 adolescent patients and 17 elderly patients (65 years of age or above) treated with cariprazine was examined. Safety measures included assessment of adverse events (AEs), clinical laboratory values, physical examinations, extrapyramidal symptom (EPS)-, depression-, and suicidality rating scales. Safety parameters were summarized using descriptive statistics. Results indicate that cariprazine was generally safe and well tolerated. Adverse events in the marginal age populations were comparable to the adult population, except for less insomnia in the young and no reports of akathisia in the elderly. Laboratory parameters, vital sign values and EEG parameters were comparable to previously published data in the adult population. In conclusion, cariprazine in the approved adult dose-range of 1.5–6 mg might be a safe treatment option also in adolescent and elderly patients with schizophrenia. Further studies are need to verify these preliminary findings.